Clinical subtypes and genetic heterogeneity: of lumping and splitting in Parkinson disease. Issue 6 (December 2016) - von Coelln, Rainer; Shulman, Lisa M.
Abstract : Purpose of review: Recent studies on clinical, genetic and pathological heterogeneity of Parkinson disease have renewed the old debate whether we should think of Parkinson disease as one disease with variations, or as a group of independent diseases that happen to present with similar phenotypes. Here, we provide an overview of where the debate is coming from, and how recent findings in clinical subtyping, genetics and clinico-pathological correlation have shaped this controversy over the last few years. Recent findings: New and innovative clinical diagnostic criteria for Parkinson disease have been proposed and await validation. Studies using functional imaging or wearable biosensors, as well as biomarker studies, provide new support for the validity of the traditional clinical subtypes of Parkinson disease (tremor-dominant versus akinetic-rigid or postural instability/gait difficulty). A recent cluster analysis (as unbiased data-driven approach to subtyping) included a wide spectrum of nonmotor variables, and showed correlation of the proposed subtypes with disease progression in a longitudinal analysis. New genetic factors contributing to Parkinson disease susceptibility continue to be identified, including rare mutations causing monogenetic disease, common variants with small effect size and risk factors (like mutations in the gene for glucocerebrosidase) that fall in between the two other categories. Recent studies show some limited correlation between genetic factors and clinical heterogeneity. Despite some variations in patterns of pathology, Lewy bodies are still the hallmark of Parkinson disease, including the vast majority of genetic subgroups. Summary: Evidence of clinical, genetic and pathological heterogeneity of Parkinson disease continues to emerge, but clearly defined subtypes that hold up in more than one of these domains remain elusive. For research to identify such subtypes, splitting is likely the way forward; until then, for clinical practice, lumping remains the more pragmatic approach.